The Effects of Irisin Hormone on Seminal Vesicle Fluid in Male Rats Administered Paroxetine - Bulmus, Ozgur; Bulmus, Funda Gulcu; Serhatlioglu, Ihsan; Canpolat, Sinan (Wiley, 2023)
[Abstract Not Available]
Keywords: Paroxetin; Irisin; Seminal vesicle; Rat